Etika Kerja Islami dan Pencegahan Malpraktik - Fathoni, Wiildan; Wahyuni, Sri; Ansori, Ansori; Yusup, Muhammad (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Islamic work ethic constitutes an essential foundation in building educational governance that is characterized by integrity and professionalism. Islamic values such as trustworthiness (amanah), honesty, discipline, responsibility, and itqan position work as a form of worship that must be carried out optimally. This study aims to analyze the internalization of Islamic work ethic in strengthening educators’ integrity and in preventing human resource management (HRM) malpractice in education at SMPN 22 Batanghari. This research employed a qualitative approach with a descriptive design. The research subjects included the principal, vice principal, teachers, and educational staff selected through purposive sampling. Data were collected through in-depth interviews, non-participant observation, and documentation studies. Data analysis was conducted interactively through data reduction, data display, and conclusion drawing, while data validity was ensured through triangulation and member checking. The findings reveal that the implementation of Islamic work ethic at SMPN 22 Batanghari significantly contributes to strengthening individual integrity and organizational culture within the school. Values such as trustworthiness, justice, and service orientation are effective in reducing the potential for malpractice, including grade manipulation, abuse of authority, and disciplinary violations. Furthermore, clear, accountable, and Islamic value-based ethical policies and procedures for handling violations support the creation of professional and transparent school governance. This study confirms that the integration of Islamic work ethic, integrity-based leadership, and effective supervision systems is a key factor in preventing HRM malpractice and improving the quality of educational services in a sustainable manner.